GC-MS and PCA Analysis of Fatty Acid Profile in Various Ilex Species - Zwyrzykowska-Wodzińska, Anna; Jarosz, Bogdan; Okińczyc, Piotr; Szperlik, Jakub; Bąbelewski, Przemysław; Zadák, Zdeněk; Jankowska-Mąkosa, Anna; Knecht, Damian (Molecules (Basel, Switzerland), 2024)
Natural compounds are important source of desired biological activity which helps to improve nutritional status and brings many health benefits. Ilex paraguariensis St. Hill. which belongs to the family Aquifoliaceae is a plant rich in bioactive substances (polyphenols, saponins, alkaloids) with therapeutic potential including hepatic and digestive disorders, arthritis, rheumatism, and other inflammatory diseases, obesity, hypertension, hypercholesterolemia. In terms of phytochemical research I. paraguariensis has been the subject of most intensive investigations among Ilex species. Therefore, we concentrated on other available Ilex varieties and focused on the content of fatty acids of these shrubs. The fatty acid compounds present in Ilex sp. samples were analyzed by GC-MS. 27 different fatty acids were identified in the extracts. The results showed that many constituents with significant commercial or medicinal importance were present in high concentrations. The primary component in all samples was α linolenic acid(18:3 Δ9,12,15). Differences of this component concentration were observed between cultivars and extensively analyzed by PCA, one- way ANOVA and Kruskal-Wallis ANOVA. Significant correlations between compound concentrations were reported.
Keywords: Phytochemicals; GC-MS; PCA; Principal Component Analysis; correlation matrix; Ilex sp.; analýza hlavních komponent; fytonutrienty; Ilex paraguariensis; rostlinné extrakty; plynová chromatografie s hmotnostně spektrometrickou detekcí; Plant Extracts; fatty acids; Gas Chromatography-Mass Spectrometry; Fatty Acids; mastné kyseliny; Ilex